Blonanserin-containing patch

JP7640498B2Active Publication Date: 2025-03-05HISAMITSU PHARM CO INC

Patent Information

Application Number
JP2022123159
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-04
Filing Date
2022-08-02
Publication Date
2025-03-05
Estimated Expiration
2042-08-02

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、ブロナンセリンの皮膚透過性に優れる、ブロナンセリン及びゴム系粘着基剤を含有する貼付剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640498000001
    Figure 0007640498000001
  • Figure 0007640498000002
    Figure 0007640498000002
  • Figure 0007640498000003
    Figure 0007640498000003
Patent Text Reader

Abstract

To provide a patch containing blonanserin and a rubber adhesive base, which is excellent in skin penetrability of blonanserin.SOLUTION: A patch has an adhesive layer on a support. The adhesive layer contains blonanserin or a pharmaceutically acceptable salt thereof, a rubber adhesive base, acetic acid, acetate, and liquid paraffin. In the adhesive layer, the mass ratio between blonanserin and acetic acid is 1: 0.05-1: 3, and the mass ratio between blonanserin and acetate is 1: 0.05-1: 3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a patch containing blonanserin. [Background technology]

[0002] 2-(4-Ethyl-1-piperazinyl)-4-(4-fluorophenyl)-5,6,7,8,9,10-hexahydrocycloocta[b]pyridine (hereafter referred to as blonanserin) is used in clinical settings as a treatment for schizophrenia, and has recently been sold as a patch (trade name: Lonasen (registered trademark) Tape).

[0003] The characteristics of patches containing blonanserin have been studied. Patent Document 1 describes that patches containing blonanserin and an acrylic adhesive suppress the production of metabolites and can maintain a sustained blood drug concentration. Patent Document 2 describes that patches containing blonanserin, an acrylic polymer, lactic acid, and a specific stabilizer maintain a sufficient blood concentration for the efficacy of blonanserin and have excellent storage stability. Patent Document 3 describes that patches containing blonanserin, lactic acid, and a specific additive have excellent skin permeability of blonanserin.

[0004] Most of the blonanserin-containing patches that have been studied so far have been patches containing an acrylic adhesive base, and there has been insufficient research on patches containing a rubber adhesive base. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2007 / 142295 [Patent Document 2] JP 2016-130269 A [Patent Document 3] International Publication No. 2012 / 105624 Summary of the Invention [Problem to be solved by the invention]

[0006] The present inventors have investigated the skin permeability of blonanserin in a patch containing blonanserin and a rubber-based adhesive base and found that the skin permeability may be insufficient in some cases. Therefore, an object of the present invention is to provide a patch containing blonanserin and a rubber-based adhesive base which has excellent skin permeability of blonanserin. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors discovered that a patch containing acetic acid and an acetate salt at a specified mass ratio to blonanserin, and further containing liquid paraffin, has excellent skin permeability of blonanserin, and thus completed the present invention.

[0008] That is, the patch of the present invention comprises an adhesive layer on a support, the adhesive layer containing blonanserin or a pharma- ceutically acceptable salt thereof, a rubber-based adhesive base, acetic acid, an acetate, and liquid paraffin, the mass ratio of blonanserin to acetic acid in the adhesive layer being 1:0.05 to 1:3, and the mass ratio of blonanserin to acetate in the adhesive layer being 1:0.05 to 1:3. Effect of the Invention

[0009] According to the present invention, it is possible to provide a patch containing blonanserin and a rubber adhesive base, which has excellent skin permeability of blonanserin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below by showing embodiments of the present invention.

[0011] A patch according to one embodiment of the present invention comprises an adhesive layer on a support, the adhesive layer containing blonanserin or a pharma- ceutically acceptable salt thereof, a rubber-based adhesive base, acetic acid, an acetate, and liquid paraffin, the mass ratio of blonanserin to acetic acid in the adhesive layer being 1:0.05 to 1:3, and the mass ratio of blonanserin to acetate in the adhesive layer being 1:0.05 to 1:3.

[0012] The support may be any material capable of maintaining the shape of the patch, particularly the pressure-sensitive adhesive layer. Examples of the material of the support include synthetic resins such as polyethylene, polypropylene, polybutadiene, ethylene-vinyl chloride copolymer, polyvinyl chloride, polyamides such as nylon, polyesters, cellulose derivatives, and polyurethanes. The properties of the support include, for example, films, sheets, sheet-like porous bodies, sheet-like foams, cloths such as woven fabrics, knitted fabrics, and nonwoven fabrics, and laminates thereof. The thickness of the support is not particularly limited, but is usually preferably about 2 μm to 3000 μm.

[0013] The adhesive layer is formed from an adhesive composition obtained by mixing blonanserin or a pharma- ceutically acceptable salt thereof, a rubber-based adhesive base, acetic acid, an acetate, liquid paraffin, and optional components described below. The mass per unit area of ​​the adhesive layer is not particularly limited, and is preferably 30 g / m. 2 ~400g / m 2 and 40 g / m 2 ~300g / m 2 , 40g / m 2 ~200g / m 2 , or 60 g / m 2 ~180g / m 2 The pressure-sensitive adhesive layer may have a mass per unit area of ​​400 g / m 2 If the mass per unit area of ​​the adhesive layer exceeds 30 g / m, the patch will be easily removed when putting on or taking off clothes. 2 If it is less than this, the adhesiveness of the patch is likely to decrease.

[0014] The pharmacy acceptable salt of Blonanserin means an acid addition salt of Blonanserin that can be used as a medicine. Examples of organic acids include formic acid, acetic acid, adipic acid, citric acid, tartaric acid, methanesulfonic acid, fumaric acid, maleic acid, etc. Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc. Blonanserin or a pharmacy acceptable salt thereof may be an anhydride or a hydrate.

[0015] The content of blonanserin can be 1% by mass to 20% by mass based on the total mass of the adhesive layer, and may be 3% by mass to 20% by mass, 3% by mass to 15% by mass, 3% by mass to 11% by mass, 3% by mass to 7% by mass, or 6% by mass to 10% by mass. Note that, in the case of a patch in which a pharma- ceutical acceptable salt of blonanserin is contained in the adhesive layer, the above-mentioned % by mass means the % by mass of blonanserin converted into its free form.

[0016] Examples of rubber-based adhesive bases include natural rubber, polyisobutylene, alkyl vinyl ether (co)polymers, polyisoprene, polybutadiene, styrene-butadiene copolymers, styrene-isoprene copolymers, and styrene-isoprene-styrene block copolymers (SIS). The rubber-based adhesive base may be used alone or in combination of two or more of these. Among these, the rubber-based adhesive base according to the present embodiment is preferably a styrene-isoprene-styrene block copolymer, polyisobutylene, or a combination thereof, from the viewpoint that the adhesive layer tends to exhibit more sufficient adhesive strength.

[0017] Specific examples of rubber-based adhesives include Quintac (registered trademark) 3570C (trade name, manufactured by Zeon Corporation), SIS5002, SIS5229, SIS5505, SIS5505P (trade names, manufactured by JSR Corporation), SIBSTAR (registered trademark) T102 (trade name, manufactured by Kaneka Corporation), and the like. Polyisobutylene also includes so-called butyl rubber (isobutylene-isoprene rubber), and specific examples thereof include Oppanol (registered trademark) N50, N80, N100, Examples of Butyl Butyl include N150, B11, B12, B50, B80, B100, B120, B150, and B220 (trade names, manufactured by BASF), JSR Butyl 065, 268, and 365 (trade names, manufactured by JSR Corporation), X_Butyl (registered trademark) RB100, 101-3, 301, and 402 (trade names, manufactured by ARLANXEO), and Exxon (registered trademark) Butyl 065, 065S, 068, 068S, 268, 268S, 365, and 365S (trade names, manufactured by ExxonMobile).

[0018] The content of the rubber-based adhesive base can be 10% by mass to 90% by mass, or may be 15% by mass to 60% by mass, 15% by mass to 40% by mass, or 15% by mass to 30% by mass, based on the total mass of the adhesive layer.

[0019] The adhesive layer contains acetic acid and an acetate salt together with liquid paraffin, and thus has excellent skin permeability of Blonanserin. Examples of acetate salts include sodium acetate, calcium acetate, and potassium acetate, and one of these may be used alone or two or more may be used in combination. The preferred acetate salt is sodium acetate.

[0020] The content of acetic acid can be 0.1% by mass to 10% by mass, and may be 0.2% by mass to 10% by mass, 0.4% by mass to 10% by mass, 0.2% by mass to 6% by mass, 0.4% by mass to 4.5% by mass, or 2% by mass to 4.5% by mass, based on the total mass of the adhesive layer. The content of acetate can be 0.1% by mass to 10% by mass, and may be 0.2% by mass to 10% by mass, 0.4% by mass to 10% by mass, 0.2% by mass to 6% by mass, 0.4% by mass to 4.5% by mass, or 1.4% by mass to 4.5% by mass, based on the total mass of the adhesive layer. For excellent skin permeability of Blonanserin, the mass ratio of Blonanserin to acetic acid in the adhesive layer is 1:0.05-1:3, may be 1:0.25-1:3, preferably 1:0.05-1:2, more preferably 1:0.06-1:0.7, and particularly preferably 1:0.3-1:0.7. The mass ratio of Blonanserin to acetate in the adhesive layer is 1:0.05-1:3, may be 1:0.22-1:3, preferably 1:0.05-1:2, more preferably 1:0.06-1:0.7, and particularly preferably 1:0.2-1:0.7. The above mass ratio means the mass ratio of Blonanserin in terms of free form when the adhesive layer contains a pharma- ceutical acceptable salt of Blonanserin.

[0021] The adhesive layer contains liquid paraffin together with acetic acid and an acetate, thereby providing excellent skin permeability of blonanserin. Specific examples of liquid paraffin include Hicol M-222, Hicol M-352 (trade names, manufactured by Kaneda Co., Ltd.), Hydrobrite HV, and Hydrobrite 1000 (trade names, manufactured by Sonneborn). When the adhesive layer contains liquid paraffin, the content of liquid paraffin is, for example, 3% by mass to 50% by mass, preferably 5% by mass to 50% by mass, more preferably 6% by mass to 45% by mass, and particularly preferably 13% by mass to 41% by mass, based on the total mass of the adhesive layer.

[0022] Since patches containing lactic acid and a rubber-based adhesive base tend to have reduced skin permeability of blonanserin, it is preferable that the adhesive layer does not contain lactic acid.

[0023] The adhesive layer may further contain other additives as desired, such as tackifier resins, plasticizers (except for liquid paraffin), absorption promoters, solubilizers, stabilizers, fillers, and fragrances.

[0024] The tackifier resin is a component that adjusts the adhesiveness of the adhesive layer. Examples of the tackifier resin include petroleum resins, terpene resins, rosin resins, phenolic resins, and xylene resins. Examples of the petroleum resin include alicyclic petroleum resins (alicyclic saturated hydrocarbon resins, etc.), aliphatic petroleum resins (aliphatic hydrocarbon resins, etc.), and aromatic petroleum resins. More specifically, Arcon P-70, Arcon P-85, Arcon P-90, Arcon P-100, Arcon P-115, Arcon P-125, Arcon M-70, Arcon M-85, Arcon M-90, Arcon M-100, Arcon M-115, and Arcon M-125 (all trade names, manufactured by Arakawa Chemical Industries Co., Ltd.), and Escoretz 8000 (trade name, manufactured by Esso Petrochemical Co., Ltd.). Examples of terpene resins include pinene polymers (α-pinene polymer, β-pinene polymer, etc.), terpene polymers, dipentene polymers, terpene-phenol polymers, aromatic modified terpene polymers, and pinene-phenol copolymers. More specific examples include YS Resin (YS Resin PXN (1150N, 300N), YS Resin PX1000, YS Resin TO125, YS Resin TO105, etc.), Clearon P105, Clearon M115, Clearon K100 (all trade names, manufactured by Yasuhara Chemical Co., Ltd.), and Tamanol 901 (trade name, manufactured by Arakawa Chemical Industries, Ltd.). Examples of rosin resins include hydrogenated rosin glycerin ester, very light-colored rosin, very light-colored rosin ester, and acid-modified very light-colored rosin. More specifically, Pine Crystal (KE-311, PE-590, KE-359, KE-100, etc.) (trade name, manufactured by Arakawa Chemical Industries, Ltd.) and the like can be mentioned. The tackifier resin may be one of these alone or two or more of them in combination. Among them, alicyclic saturated hydrocarbon resin, terpene resin, hydrogenated rosin glycerin ester, or a combination thereof is preferable, and alicyclic saturated hydrocarbon resin, terpene resin, or a combination thereof is more preferable. When the adhesive layer contains a tackifier resin, the content of the tackifier resin can be 15% by mass to 80% by mass, and may be 30% by mass to 65% by mass, based on the total mass of the adhesive layer.

[0025] Examples of plasticizers other than liquid paraffin include light liquid paraffin, squalane, squalene, vegetable oils (olive oil, camellia oil, castor oil, tall oil, peanut oil, spearmint oil, eucalyptus oil, jojoba oil, camphor white oil, sunflower oil, orange oil, etc.), fats and oils (dibutyl phthalate, dioctyl phthalate, etc.), and liquid rubber (liquid polybutene, liquid isoprene rubber, etc.). When the adhesive layer contains a plasticizer other than liquid paraffin, the content thereof is, for example, 3% by mass to 50% by mass, 5% by mass to 30% by mass, or 7% by mass to 20% by mass based on the total mass of the adhesive layer.

[0026] The absorption enhancer may be any compound that has been known to have a transdermal absorption enhancing effect. Examples of the absorption enhancer include organic acid esters (e.g., fatty acid esters, cinnamic acid esters), organic acid amides (e.g., fatty acid amides), aliphatic alcohols, polyhydric alcohols, ethers (e.g., aliphatic ethers, polyoxyethylene alkyl ethers), and the like. These absorption enhancers may have unsaturated bonds and may have a cyclic, linear, or branched chemical structure. In addition, the absorption enhancer may be a monoterpene compound, a sesquiterpene compound, or a vegetable oil (e.g., olive oil). These absorption enhancers may be used alone or in combination of two or more.

[0027] Examples of organic acid esters include ethyl acetate, propyl acetate, cetyl lactate, lauryl lactate, methyl salicylate, ethylene glycol salicylate, methyl cinnamate, and fatty acid esters. Examples of fatty acid esters include methyl laurate, hexyl laurate, isopropyl myristate, myristyl myristate, octyldodecyl myristate, isopropyl palmitate, and cetyl palmitate. The fatty acid ester may be glycerin fatty acid ester, propylene glycol fatty acid ester, sorbitan fatty acid ester, polyethylene glycol sorbitan fatty acid ester, polyethylene glycol fatty acid ester, sucrose fatty acid ester, or polyoxyethylene hydrogenated castor oil. Specific examples of fatty acid esters include glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monooleate, sorbitan monolaurate, sucrose monolaurate, polysorbate 20, propylene glycol monolaurate, polyethylene glycol monolaurate, polyethylene glycol monostearate, Span 40, Span 60, Span 80, Span 120 (product names, manufactured by Croda Japan Co., Ltd.), Tween (registered trademark) 20, Tween (registered trademark) 21, Tween (registered trademark) 40, Tween (registered trademark) 60, Tween (registered trademark) 80, and NIKKOL (registered trademark) HCO-60 (product name, manufactured by Nikko Chemicals Co., Ltd.).

[0028] Examples of organic acid amides include fatty acid amides (such as lauric acid diethanolamide), hexahydro-1-dodecyl-2H-azepin-2-one (also called Azone) and its derivatives, and pyrothiodecane.

[0029] The term "aliphatic alcohol" refers to an aliphatic alcohol having 6 to 20 carbon atoms. Examples of the aliphatic alcohol include lauryl alcohol, myristyl alcohol, oleyl alcohol, isostearyl alcohol, and cetyl alcohol. Examples of the polyhydric alcohol include propylene glycol.

[0030] The aliphatic ether means an ether having an aliphatic group (for example, an alkyl group, an alkenyl group) having 6 to 20 carbon atoms. An example of the polyoxyethylene alkyl ether is polyoxyethylene lauryl ether.

[0031] Examples of the monoterpene compounds include geraniol, thymol, terpineol, l-menthol, borneol, d-limonene, isoborneol, nerol, and dl-camphor. As the monoterpene compound, peppermint oil may be used.

[0032] When the pressure-sensitive adhesive layer contains an absorption enhancer, the content of the absorption enhancer can be 2% by mass to 40% by mass based on the total mass of the pressure-sensitive adhesive layer.

[0033] The solubilizer is a component that makes it easy to dissolve blonanserin or a pharma- ceutically acceptable salt thereof in the adhesive composition. Examples of the solubilizer include fatty acid alkyl esters (e.g., isopropyl myristate, isopropyl palmitate), fatty acid polyhydric alcohol esters (e.g., propylene glycol monolaurate, glycerin monolaurate, glycerin monooleate, sorbitan monolaurate), fatty acid amides (e.g., diethanolamide laurate), fatty alcohols (e.g., octyldodecanol, isostearyl alcohol, oleyl alcohol), polyhydric alcohols (e.g., propylene glycol, dipropylene glycol, polyethylene glycol), and pyrrolidone derivatives (e.g., N-methyl-2-pyrrolidone). When the adhesive layer contains a solubilizer, the content of the solubilizer can be 2% by mass to 40% by mass based on the total mass of the adhesive layer.

[0034] The stabilizer may be any that can suppress the generation of free radicals generated by the action of light such as ultraviolet rays, heat, or active chemical species, and the progression of the chain reaction thereof. Examples of the stabilizer include tocopherol and its ester derivatives, ascorbic acid and its ester derivatives, 2,6-dibutylhydroxytoluene (BHT), butylhydroxyanisole (BHA), and 2-mercaptobenzimidazole. The stabilizer may be used alone or in combination of two or more. When the adhesive layer contains a stabilizer, the content of the stabilizer may be 0.05% by mass to 3% by mass, or may be 0.05% by mass to 1% by mass, 0.05% by mass to 0.25% by mass, or 0.1% by mass to 0.25% by mass, based on the total mass of the adhesive layer.

[0035] Examples of the filler include powders of metal compounds (aluminum oxide, aluminum hydroxide, zinc oxide, titanium oxide, calcium carbonate, etc.), ceramics (talc, clay, kaolin, silica, hydroxyapatite, synthetic aluminum silicate, magnesium aluminometasilicate, etc.), or organic compounds (cellulose powder, stearates, etc.), or short fibers of resins containing these. When the pressure-sensitive adhesive layer contains a filler, the content of the filler can be 0.1% by mass to 20% by mass based on the total mass of the pressure-sensitive adhesive layer.

[0036] The patch may further comprise a release liner. The release liner is laminated on the surface of the adhesive layer opposite to the support. The release liner tends to reduce adhesion of dirt and the like to the adhesive layer during storage. The surface of the release liner that comes into contact with the adhesive layer is preferably release-treated with silicone, fluorinated polyolefin, or the like.

[0037] The material of the release liner is not particularly limited, and liners generally known to those skilled in the art can be used. Examples of the release liner include paper; polyesters such as polyethylene terephthalate and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene; and films such as polyvinyl chloride, polyvinylidene chloride, nylon, and aluminum. The release liner may be a laminate film of high-quality paper and polyolefin. The material of the release liner is preferably a film made of polypropylene or polyethylene terephthalate.

[0038] The patch can be produced, for example, by the following method, but is not limited thereto, and any known method can be used. First, the components constituting the adhesive layer are mixed in a predetermined ratio to obtain a uniform solution (adhesive composition). Next, the adhesive composition is spread on a peelable film (release liner) at a predetermined mass per unit area to form an adhesive layer. Furthermore, a support is pressed onto the adhesive layer so that the adhesive layer is sandwiched between the release liner and the support. Finally, the patch can be obtained by cutting into the desired shape and dimensions. In this case, the release liner is removed when the patch is applied. The area of ​​the patch is 1 to 200 cm. 2 5 to 100 cm 2 30 to 80 cm 2 The shape and dimensions of the patch may be, for example, a rectangle with a short side of 3 to 14 cm and a long side of 7 to 20 cm, or a circle with a diameter of 1 to 10 cm. EXAMPLES

[0039] Test Example 1: Evaluation of the presence or absence of lactic acid in patches containing rubber-based adhesive bases 1. Manufacturing of patches A pressure-sensitive adhesive composition was obtained by mixing the components according to the following Table 1. The pressure-sensitive adhesive composition thus obtained was applied onto a release liner (a polyethylene terephthalate film subjected to a release treatment) in an amount of 80 g / m2 per unit area. 2The solvent was then dried and removed to form an adhesive layer. A support layer (a polyethylene terephthalate film) was laminated on the opposite surface of the obtained adhesive layer to obtain a patch laminated in this order: support layer / adhesive layer / release liner.

[0040] 2. Hairless mouse skin permeability test The patch is then spread to a thickness of 2 cm. 2 A hairless mouse was punched out into a 3 mm diameter hole, fat was removed from the excised skin, and a patch with the release liner removed was applied to the epidermis side. This was set in a flow-through Franz-type permeation test cell so that the dermis side was in contact with the receptor side, and the cell was filled with receptor solution (physiological saline). Next, the receptor solution was delivered while circulating heated circulating water around the periphery so that the receptor solution was kept at 32°C, and the receptor solution was collected every 2 hours for up to 24 hours. The concentration of blonanserin in the collected receptor solution was measured by high performance liquid chromatography, and the cumulative skin permeation amount of blonanserin (μg / cm) from the start of application to 24 hours was calculated. 2 ) and maximum skin permeation rate (μg / cm 2 / hr) was calculated. <Analysis conditions> Column: TSK gel ODS-80TsQA 5μm (4.6mm I.D. x 150mm) Mobile phase: 0.5% phosphoric acid:acetonitrile = 73:27 Measurement wavelength: 248nm Flow rate: 1ml / min Column temperature: 40℃

[0041] [Table 1]

[0042] It was confirmed that the patch of Comparative Example 2 containing lactic acid had extremely low skin permeability of blonanserin compared to the patch of Comparative Example 1 not containing lactic acid.

[0043] Test Example 2: Evaluation of patches containing acetic acid and sodium acetate (1) As in Test Example 1, patches were prepared according to the compositions in Table 2 below, and a hairless mouse skin permeability test was carried out.

[0044] [Table 2]

[0045] It was confirmed that the patches of Examples 1 to 5 (patches of blonanserin:acetic acid=1:0.06 to 1:0.65, and blonanserin:sodium acetate=1:0.06 to 1:0.67) were excellent in skin permeability.

[0046] Test Example 3: Evaluation of patches containing alicyclic saturated hydrocarbon resin, terpene resin, and hydrogenated rosin glycerin ester as tackifier resins In the same manner as in Test Example 1, patches were prepared according to the composition in Table 3 below, and a hairless mouse skin permeability test was carried out. 2 The patches were punched out and applied to mice.

[0047] [Table 3]

[0048] It was confirmed that the patches of Examples 6 to 8 had excellent skin permeability of blonanserin.

[0049] Test Example 4: Evaluation of patches containing liquid paraffin In the same manner as in Test Example 1, patches were prepared according to the composition in Table 4 below, and a hairless mouse skin permeability test was carried out. 2 The patches were punched out and applied to mice.

[0050] [Table 4]

[0051] It was confirmed that the patches of Examples 9 to 12 (patches containing liquid paraffin) were excellent in skin permeability of blonanserin.

[0052] Test Example 5: Evaluation of patches containing acetic acid and sodium acetate (2) As in Test Example 1, patches were prepared according to the compositions in Table 5 below, and a hairless mouse skin permeability test was carried out.

[0053] [Table 5]

[0054] In the patch of Comparative Example 6 (patch with blonanserin:acetic acid=1:0.03, blonanserin:sodium acetate=1:0.03), although it contains acetic acid, sodium acetate, and liquid paraffin, the mass ratios of blonanserin to acetic acid and the mass ratios of blonanserin to sodium acetate are outside the ranges of these mass ratios in the patch of the present invention, and therefore it was confirmed that the skin permeability of blonanserin is low even when compared with the patch of Comparative Example 7 (patch not containing liquid paraffin). It was confirmed that the patches of Examples 13 to 15 (patches with blonanserin:acetic acid=1:0.25 to 1:3, blonanserin:sodium acetate=1:0.22 to 1:3) are superior in skin permeability of blonanserin compared with the patches of Comparative Examples 5 to 7.

Claims

1. A patch comprising a support and an adhesive layer, the adhesive layer contains blonanserin or a pharma- ceutically acceptable salt thereof, a rubber-based adhesive base, acetic acid, an acetate, and liquid paraffin; the mass ratio of blonanserin to acetic acid in the adhesive layer is 1:0.05 to 1:3; The mass ratio of blonanserin to acetate in the adhesive layer is 1:0.05 to 1:

3. Patch.

2. The patch according to claim 1 , wherein the adhesive layer does not contain lactic acid.

3. The patch according to claim 1 or 2, wherein the acetate is sodium acetate.

4. 3. The patch according to claim 1, wherein the rubber-based adhesive base is a styrene-isoprene-styrene block copolymer, polyisobutylene, or a combination thereof.

Citation Information

Patent Citations

  • Percutaneous absorption promoter, pharmaceutical composition comprising the same, and adhesive preparation

    JP2012140407A

  • Patch formulation

    JP2016130269A

  • Patches for external use

    WO2001007018A1

  • Pasting preparation

    WO2005115355A1

  • Novel tape preparation

    WO2007142295A1

Cited By

  • Blonanserin-containing patch

    JP2024077124A